(untitled) (Global Journal of Human-Social Science, 2012)
Waste management problems result from indiscriminate waste disposal which stems from Inadequate planning and implementation. This fact led to the present study which applied the Techniques of gis and rs to disposal sites and transport route selection in the emerging Megacity of abeokuta. Spatial data such as land-cover types; road and drainage networks of the City were extracted from a geo-referenced high resolution satellite image through on-screen Digitizing using gis softwares such as arcview. The existing disposal sites were geo-located And added as a layer to the map of the city. The land-cover, drainages, and roads were buffered at 30, 160 and 200 meters respectively using preset criteria such as distance of site from a street at 30 m, surface water at 160 m, major roads at 200 m and absence of important economic or Ecological features; to determine candidate sites from the land-cover types. Four legal disposal Sites in saje, olomore, totoro and ita-oshin and patches of illegal disposal sites were identified. Gis analysis gave a total of nine sites out of which only four met the preset criteria. Saje, ita -Oshin, sam-ewang, and ita-ika areas were the most appropriate sites.